SOME ASPECTS OF STUDENTS’ PHYSICAL EDUCATION AND SANITARY ACTIVITIES - Маракушин, Андрій; Мкртічян, Оксана (New Collegium, 2020)
The article discusses the actual problems of using various ways of physical education, sanitary and recreational leisure activities, sports, tourism; the importance of the rationalization the spare time by students, the formation of the ability to choose interesting and useful types of leisure. Physical development starts from the very childhood, it develops both during classes (physical training minutes during lessons, games and exercises at breaks and in the extended day mode), and at lessons of physical education and some others, at breaks, during walks, socially useful work, in play activities, while organizing leisure. Being active in physical education and sanitary activities is a prerequisite for the harmonious development of student youth, which acquires the qualities of purposeful influence on a particular person according to his needs, interests, abilities. The main directions of active education and sanitary activities were defined. They included: implementing democratic types of physical activity into student’s leisure, increasing advertisements concerning conducting a healthy lifestyle by the mass media, implementing services of animators, new technologies in the work of objects in the field of leisure and recreation, development of alternative forms and types of active leisure, increasing attention to national traditions in the field of physical education and sanitary activities.